Stress and its associated factors amongst ward nurses in a public hospital Kuala Lumpur. - Syed Yahya, Sharifah Zainiyah; I. M., Afiq; Chow, C. Y.; D. , Siti Sara (Malaysian Public Health Specialist Association, 2011)
Occupational stress exists in all professions, but the nursing profession appears to experience more stress at work compared to other health care workers. Stressful conditions at the workplace may cause the high turnover and burnout among nurses. This study objective was to determine the level of stress and its associated factors among in-patient ward nurses. A cross sectional study using the stratified random sampling method was carried out among 114 staff nurses from 5 different departments in a public hospital in Kuala Lumpur. Respondents were requested to complete a single set of validated and self-administered questionnaire, the Depression, Anxiety, Stress Scale (DASS) . Data was analysed using SPSS 17. In general, the prevalence of stress at the department of Medicine was found to be higher compared to other departments studied. There was also a statistical significant relationship between the prevalence of stress and types of department (p<0.05). The association between prevalence of stress and age, marital status, financial status and working shift were not found to be statistically significant (p > 0.05). In conclusion, stress had no significant association with socio-demographic factors (age, marital status and financial status) and working environment except for type of department nurses work in. There might be some other possible confounders that have a bigger potential in becoming stressors compared to those independent variables in this study.